Detection of Class 1 Integron Encoding Gene in Multidrug Resistance (MDR) Citrobacter freundii Isolated from Healthy Broiler Chicken - A. M. Witaningrum; F. J. Wibisono; D. A. Permatasari; M. H. Effendi (Faculty of Animal Science, Bogor Agricultural University, 2021)
This study was aimed to find out that broiler chicken farms have problems with antibiotic resistance Citrobacter freundii and determined the prevalence and class 1 integron encoding gene. Multidrug resistance Citrobacter freundii was collected from broiler chicken among one hundred and sixty cloacal swab samples from 32 farms in Blitar for 3 months. The method of bacterial inoculation used MacConkey agar and biochemical test was conducted by IMViC and TSIA test. Citrobacter freundii for antibiotic sensitivity pattern was tested by disk diffusion, and the multidrug resistance encoding gene was tested by PCR. This study exposed 160 samples, and 13.75% (22/160) samples were positive of Citrobacter freundii. The antibiotic sensitivity pattern showed high resistances against ampicillin and erythromycin (77.27%), tetracycline (59.09%), trimetropim-sulfamethoxazole (50%), and streptomycin (22.72%). Isolates that were detected as multidrug resistance were continued with PCR testing to prove the existence of a class 1 integron encoding gene. Multidrug resistance Citrobacter freundii isolated from broiler chicken farms in Blitar were 81.82% (18/22), and were indicated that five were positive Class 1 Integron encoding gene. The results of this study showed that the prevalence and distribution of multidrug resistance Citrobacter freundii were high, so it can cause the spread of antimicrobial resistance to public health. Class 1 integron encoding gene was found 22.72% from multidrug resistance Citrobacter freundii by PCR. It was concluded that broiler chicken farms need assessment management to reduce and avoid multidrug resistance bacteria in animals and human. Therefore, the use of appropriate antibiotics is a good step to reduce the incidence of MDR in poultry.